2010
DOI: 10.1039/b925708j
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable, protein resistant thin films on SiC-modified silicon substrates

Abstract: Thin films terminated with oligo(ethylene glycol) (OEG) could be photochemically grafted onto ultrathin silicon carbide layers that were generated on silicon substrates via carbonization with acetylene at 820 degrees C. The OEG coating reduced the non-specific adsorption of fibrinogen on the substrates by 99.5% and remained resistant after storage in PBS for 4 weeks at 37 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Ourselves and others have developed monolayers presenting OEG, which are directly bound on non-oxidized silicon substrates via Si–C bonds 7,9,16–19. Formation of the Si–C bonds is via surface hydrosilylation on hydrogen-terminated silicon surfaces,2022 using OEG25 terminated alkenes, such as 1 in Scheme 1 9,1719,23. Our OEG-terminated monolayers are highly protein-resistant and stable in phosphate-buffered saline (PBS) 19.…”
Section: Introductionmentioning
confidence: 99%
“…Ourselves and others have developed monolayers presenting OEG, which are directly bound on non-oxidized silicon substrates via Si–C bonds 7,9,16–19. Formation of the Si–C bonds is via surface hydrosilylation on hydrogen-terminated silicon surfaces,2022 using OEG25 terminated alkenes, such as 1 in Scheme 1 9,1719,23. Our OEG-terminated monolayers are highly protein-resistant and stable in phosphate-buffered saline (PBS) 19.…”
Section: Introductionmentioning
confidence: 99%
“…HCl (5.72 mL, 57.2 mmol) was added dropwise at 0 8C. Then, the reaction mixture was warmed to rt and stirred for 24 h. After this period, the solvent was concentrated in vacuum and the crude reaction mixture was basified with ammonia to pH 8, then extracted with ethyl acetate, and the organic layer was dried over 1, 140.9, 140.5, 139.2, 135.0, 134.7, 133.8, 132.8, 132.5, 132.1, 131.9, 130.2, 129.1, 128.7, 123.5, 114.8, 22.3, 20.1, 19.9, 19.8 2',2''', 5',4,5,3,2-dioxaborolan-2-yl)-[1,1':4',1'':4'',1'''-quaterphenyl]-4-amine ( 15).F ollowing the procedure outlined for 8,c ompound 14 (805 mg, 1.76 mmol), bis(pinacolato)diboron (508 mg, 2.0 mmol), Pd(dppf) 2 Cl 2 (219 mg, 0.36 mmol), and KOAc (530 mg, 5.41 mmol) in anhydrous DME (26 mL) 2, 144.1, 142.3, 140.8, 140.3, 140.2, 140.0, 138.1, 132.7, 132.0, 131.9, 131.6, 131.5, 130.2, 128.9, 128.7, 114.8, 83.5, 24.9, 21.7, 20.1, 20.0, 19.8 4 (77 mg, 0.07 mmol), AgCO 3 (827 mg, 3.0 mmol), and anhydrous THF (40 mL) as the solvent. The mixture was stirred at rt for 12 h. Column chromatography (SiO 2 ;c yclohexane/EtOAc, 1:1) gave compound 16 as ay ellowish syrup (200 mg 3, 143.2, 140.9, 140.8, 140.6, 140.4, 140.1, 140.0, 136.4, 136.3, 132.8, 132.7, 132.6, 132.1, 132.0, 132.0, 131.3, 130.2, 129.1, 128.9, 114.9, 107.7, 60.5, 20.1, 20.0, 0.1 ppm.…”
Section: Generale Xperimental Methodsmentioning
confidence: 99%
“…[13] In this regard, SiÀOb onds are not preferred for many biological applicationsd ue to their demonstrated limited biocompatibility and stability. [14] To overcome this limitation, several alternatives have been proposed, such as generating ultrathin layers of silicon carbideo ns ilicon substrates [15] or by covering the silicon surfacew ith alkynylo ra lkenyl derivatives via SiÀC bonds, which are more stable bonds and this increases the coveragey ields. [16] In both cases silicon-modified surfaces are superiort oS i ÀOb onds in terms of chemical stability, biocompatibility,m echanical properties, and sensitivity for electrical measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Kotzar et al showed that 3C-SiC films are biocompatible [21], a conclusion that was also reached by Coletti et al [37], who found that mammalian cell proliferation was greater on 3C-SiC surfaces than on Si surfaces (see Chapter 4). Qin et al found oligo(ethylene glycol) (OEG) photochemically grafted to ultrathin (4 nm thick) 3C-SiC layers using UV light at 254 nm were highly resistant to non-specific fibrinogen protein adsorption, reducing absorption by 95.5% [38]. Moreover, the OEG coatings were extremely stable, exhibiting essentially no loss in protein resistance after storage in PBS at 37 °C for 4 weeks.…”
Section: C-sic As a Materials For Biomemsmentioning
confidence: 99%